Can Endorectal Ultrasound, MRI, and Mucosa Integrity Accurately Predict the Complete Response for Mid-Low Rectal Cancer After Preoperative Chemoradiation? A Prospective Observational Study from a Single Medical Center. Issue 8 (August 2018) - Liu, Sen; Zhong, Guang-xi; Zhou, Wei-xun; Xue, Hua-dan; Pan, Wei-dong; Xu, Lai; Lu, Jun-yang; Wu, Bin; Lin, Guo-le; Qiu, Hui-zhong; Xiao, Yi
Abstract : BACKGROUND: Patients with locally advanced rectal cancer could be managed by a watch-and-wait approach if they achieve clinical complete response after preoperative chemoradiotherapy. Mucosal integrity, endorectal ultrasound, and rectal MRI are used to evaluate clinical complete response; however, the accuracy remains questionable. Clinical practice based on those assessment methods needs more data and discussion. OBJECTIVE: The aim of this prospective study was to evaluate the accuracy of mucosal integrity, endorectal ultrasound, and rectal MRI to predict clinical complete response after chemoradiotherapy. DESIGN: Endorectal ultrasound and rectal MRI were undertaken 6 to 7 weeks after preoperative chemoradiation therapy. Patients then received radical surgery based on the principles of total mesorectal excision. Preoperative tumor staging achieved by endorectal ultrasound and rectal MRI was compared with postoperative staging by pathologic examination. Sensitivity, specificity, and accuracy of each evaluation method were calculated. SETTINGS: The study was conducted at a single tertiary care center. PATIENTS: Patients diagnosed with mid-low rectal cancer by biopsy between May 2014 and December 2016 were enrolled in this study. RESULTS: A total of 124 patients were enrolled in this study, and postoperative pathology revealed that 20 patients (16.13%) achieved complete response (ypT0 N0 ). The sensitivity of mucosal integrity, endorectal ultrasound, and MRI to predict clinical complete response was 25%. The specificity of mucosal integrity, endorectal ultrasound, and MRI was 94.23%, 93.90%, and 93.27%. The combination of each 2 or all 3 methods did not improve accuracy. Regression analysis showed that none of these methods could predict postoperative ypT0 . LIMITATIONS: The sample size is small, and we did not focus on the follow-up data and cannot compare prognosis data with previous research studies. CONCLUSIONS: Both single-method and combined mucosal integrity, endorectal ultrasound, and rectal MRI have poor correlation with postoperative pathologic examination. A watch-and-wait approach based on these methods might not be a proper strategy compared with radical surgery after neoadjuvant therapy. SeeVideo Abstract athttp://links.lww.com/DCR/A693 . Abstract : Supplemental Digital Content is available in the text.